Role of microalgae in treatment of acid mine drainage and recovery of valuable metals. (2020) - Samal, D.P. Krishna; Sukla, Lala Behari; Pattanaik, Archana; Pradhan, Debabrata
Abstract: Discharge of acidic water associated with sulfide, pyrite with other metals from abandoned or active mines is the major cause of acid mine drainage in mining regions. The liquid discharged from mining sectors often contains harmful, toxic heavy metals such as copper, iron, sulfur, nickel and zinc. The production of acidic pH and presence of metals have adverse effect upon aquatic habitats, environment pollution that further indirectly leads to health related concern in humans and animals. So recent research work focuses on investigation of different types of microalgal species which have capacities to remove heavy metals and toxic pollutants from acid mine drainage. Currently phycoremediation is an ideal substitute method over any other conventional techniques. They made the acidic environment alkaline and also act as bioaccumulators which is required for heavy metal precipitation. Application of microorganisms like bacteria, fungus along with algae can also be an effective approach for bioremediation of acid water drainage.